The Fruit Characteristics of Ambon Forest Nutmeg (Myristica fatua Houtt) and Banda Nutmeg (Myristica fragrans Houtt) - Karmanah Karmanah; Slamet Susanto; Winarso Drajad Widodo; Edi Santosa (Institut Pertanian Bogor, 2020)
Ambon Forest nutmeg (Myristica fatua Houtt) is one of the endemic plants in Indonesia. The morphological characteristic of Ambon Forest nutmeg is slightly different from that of Banda nutmeg (Myristica fragrans Houtt) i.e., it is not used as spices, but its oil is used as a lamp oil. This study aimed to determine the chemical components and essential oils of Ambon Forest nutmeg derived from its seeds, mace, and flesh compared to Banda nutmeg. Extractions of essential oils were performed using a steam hydro-distillation. Analysis of chemical compositions and contents of essential oil was carried out using a Gas Chromatography-Mass Spectrometry (GCMS) instrument and SNI 06-2388-2006 method. The essential oil contents in Ambon Forest nutmeg were relatively low, i.e., 0.63% in the seeds, 0.30% in the mace, and 0.04% in the flesh compared to Banda nutmeg i.e., 1% in the seeds, 40% in the mace, and 3.5% in the fruit flesh. The chemical compositions of essential oils showed that M. fatua Houtt contained 12 compounds in the seeds, 24 compounds in the mace, and 17 compounds in the fruit flesh, while for Banda Nutmeg, the contents of essential oils were found 18 compounds in the seeds, 10 compounds in the mace, and 15 compounds in the fruit flesh. M. fatua Houtt contained the highest Copaene, i.e., 28.41% in the seeds, 10.42% in the mace, and 23.33% in the fruit flesh. Myristicin, as the main marker compound of nutmeg oil, was also found in Ambon Forest nutmeg i.e., 1.3% in the seeds, 1.16% in the mace, and 5.19% in the fruit flesh. However, these results showed lower contents when compared to Banda nutmeg with Myristicin contents of 8.72% in the seeds, 10.14% in the mace, and 10.46% in the fruit flesh. Keywords: Essential oil, Myristica fatua Houtt, Myristica fragrans Houtt, Nutmeg